(untitled) (Research, Society and Development, 2023)
As it is a proposal for employment and income for the semiarid region of the Northeast, Embrapa Algodão identified important technological processes related to the production and commercialization system, which enhance the yield and improve the quality of Sea Island cotton (Gossypium barbadense), variety Monserrat, whose 38 mm long fiber achieves the highest price on the planet. This work aimed to present the broad technological panorama used in the production system of extra-long fiber cotton produced by producers in Barbados, aiming to encourage and expand its cultivation in the Brazilian Semiarid region. The study is based on a narrative review of extra-long staple Sea Island cotton (Gossypium barbadense) grown in the Barbados Caribbean. Based on the results obtained in Barbados, its productivity is 2,250 Kg/ha, and its value in kilograms of raw cotton paid to the producer is estimated at over R50.00.